From the archaeological record to virtual reconstruction : the application of information technologies at an Iron Age fortified settlement (San Chuis Hillfort, Allande, Asturias, Spain) /: the application of information technologies at an Iron Age fortified settlement (San Chuis Hillfort, Allande, Asturias, Spain). (2018) - Salido, Juana Molina
No abstract available